Analisis Network Planning dengan Critical Path Method (CPM) Dalam Rangka Efisiensi Waktu dan Biaya Proyek Pembangunan Rumah Minimalis (Studi Kasus: Property Group Medan) - Lilyana Lilyana (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
The development of science and technology in the field of computers is currently so fast, along with many new discoveries that are useful in developing this technology. This greatly affects the performance of each agency and company in dealing with any problems that arise in data processing. Analysis of the application of time management in home construction construction projects, using the Microsoft Project 2007 application, is very helpful for contractors in managing home construction projects, starting from making project plans, allocating resources, planning construction project costs, making project movement plans and evaluating projects. in accordance with the provisions for completing the study in the Information Systems undergraduate program which must make a thesis.